Bluetongue and epizootic haemorrhagic disease in wildlife with emphasis on the South American scenario - Mazzoni Baldini, Maria Helena [UNESP]; De Moraes, Aury Nunes (My University, 2021)
Bluetongue and epizootic hemorrhagic disease affect domestic ruminants and cervids. However, other species may act as pathogen carriers in the transition of bluetongue virus (BTV) and epizootic hemorrhagic disease virus (EHDV). The wild species affected by these diseases manifest a variable range of clinical signs and lesions, and while some species appear to be extremely susceptible, showing high levels of mortality, some are resistant to these pathogens, acting as potential reservoirs of these orbiviruses.  The purpose of the following review is to describe the clinical and pathological manifestations related to these diseases in wild species and to review studies performed on non-domestic species in South America, emphasizing the challenges of studying infectious diseases in free-living animals and the gaps in knowledge about bluetongue and epizootic haemorrhagic disease epidemiology. These gaps should be filled by more studies on the range of species affected and the transmission mechanisms, including in domestic species.